1988
DOI: 10.1093/oxfordjournals.eurheartj.a062410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dose-effect relationship of a new ace inhibitor (perindopril) by an automatic blood pressure recorder

Abstract: Repeated blood pressure recordings by non-invasive devices are of better predictive value than single measurements in the evaluation of antihypertensive treatment. Such a method has been used to establish the dose-effect relationship of perindopril. After a two-week placebo run-in period, 40 patients with essential hypertension (age 56.6 +/- 1.5 years, 31 males, nine females) were treated with placebo or 2, 4 or 8 mg of perindopril once daily for one month following a randomized double-blind design. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…1984;Heel et a1. 1979;Luccioni et al 1988) and is consistent with the results of Weinberger (1982) showing the synergistic antihypertensive effect of the combination ACE inhibitor/diuretic. As expected, there was a significant decrease in mean heart rate with atenolo1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1984;Heel et a1. 1979;Luccioni et al 1988) and is consistent with the results of Weinberger (1982) showing the synergistic antihypertensive effect of the combination ACE inhibitor/diuretic. As expected, there was a significant decrease in mean heart rate with atenolo1.…”
Section: Discussionsupporting
confidence: 88%
“…In healthy subjects, orally administered perindopril 1 to 16mg has been shown to cause dose-dependent ORIGINAL RESEARCH ARTICLE inhibition of plasma ACE activity with the maximal effect occurring at 4 to 6 hours, and persisting ACE inhibition 24 hours after administration of 4 or 8mg (Bussien et al 1986;Lees & Reid 1987a). Previous dose-response studies have shown perindopril to have antihypertensive activity at doses of ~ 4mg once daily (Lees & Reid 1987b;Luccioni et al 1988).…”
mentioning
confidence: 99%
“…This to the active diacid metabolite perindoprilat (S 9780) long terminal phase seems to reflect the high affinity of (Laubie et al, 1984). Minor metabolic pathways lead to perindoprilat for plasma ACE and can be considered to glucuronide-conjugates (S 9490 glucuronide and S 9780 be relevant to its pharmacodynamics (Devissaguet et al, tension and of congestive heart failure (Luccioni et al, 1988;Thuillez et al, 1987). Since renal failure is often associated with these conditions and since the kidney is the main route of elimination of perindoprilat, this study was designed to investigate the influence of various degrees of renal insufficiency on the pharmacokinetics of perindopril and its main metabolites after a single oral dose.…”
Section: Introductionmentioning
confidence: 99%
“…They were included if at least 75% of diastolic blood pressure recordings, made over an 8 h diurnal period using an automatic blood pressure recorder, were greater than 95 mmHg on placebo. Treatment was significantly associated with a greater reduction of blood pressure with 4 and 8 mg/day doses compared with placebo and the 2 mg/day dose [36].…”
Section: Phase II Studies: Blood Pressure Studiesmentioning
confidence: 90%